DECODING HUMOR AND RELIGION IN INDONESIAN NAMES - Lesmana, Maman (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This article aims to explore the structure and meaning of unique Indonesian names, their origins, and the humor they encompass. The topic was selected due to its recent viral status on social media. Utilizing qualitative methods and library research, data were gathered from internet news articles and analyzed through theories of names and nicknames, humor, and Arabic and Islamic religion. These theoretical frameworks were particularly pertinent as the study revealed that many unique names are intricately linked to Islamic and Arabic elements. The findings suggest that the uniqueness of these names often arises from spontaneous selection, with minimal deliberation or understanding of the religious terms incorporated. Predominantly found among the lower-middle class, these names stand out due to their distinctiveness, which often elicits humor. The humorous aspects of these names can be categorized under incongruity theory and, in some cases, superiority theory. This research highlights the cultural and social dimensions of naming practices in Indonesia and their unintended comedic impact.